Parameters Influencing Sulfur Speciation in Environmental Samples Using Sulfur K-Edge X-Ray Absorption Near-Edge Structure - Siwatt Pongpiachan; Kanjana Thumanu; Charnwit Kositanont; Klaus Schwarzer; Jörg Prietzel; Phoosak Hirunyatrakul; Itthipon Kittikoon (Journal of Analytical Methods in Chemistry)
This paper aims to enhance the credibility of applying the sulfur K-edge XANES spectroscopy as an innovative “fingerprint” for characterizing environmental samples. The sensitivities of sulfur K-edge XANES spectra of ten sulfur compound standards detected by two different detectors, namely, Lytle detector (LyD) and Germanium detector (GeD), were studied and compared. Further investigation on “self-absorption” effect revealed that the maximum sensitivities of sulfur K-edge XANES spectra were achieved when diluting sulfur compound standards with boron nitride (BN) at the mixing ratio of 0.1%. The “particle-size” effect on sulfur K-edge XANES spectrum sensitivities was examined by comparing signal-to-noise ratios of total suspended particles (TSP) and particulate matter of less than 10 millionths of a meter (PM10) collected at three major cities of Thailand. The analytical results have demonstrated that the signal-to-noise ratios of sulfur K-edge XANES spectra were positively correlated with sulfate content in aerosols and negatively connected with particle sizes. The combination of hierarchical cluster analysis (HCA) and principal component analysis (PCA) has proved that sulfur K-edge XANES spectrum can be used to characterize German terrestrial soils and Andaman coastal sediments. In addition, this study highlighted the capability of sulfur K-edge XANES spectra as an innovative “fingerprint” to distinguish tsunami backwash deposits (TBD) from typical marine sediments (TMS).